2011
DOI: 10.1111/j.1439-0426.2011.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-phenoxyethanol anaesthesia on juvenile meagre (Argyrosomus regius)

Abstract: This study was performed to evaluate the effective concentration of the anaesthetic 2-phenoxyethanol (2-PE) on juvenile (1.3 ± 0.03 g) meagre (Argyrosomus regius, Asso, 1801) and establish the LC 50 (through a series of exposure concentrations) and LT 50 of 2-PE at 20 ± 0.5°C, salinity 38 g · L )1 , pH 8.2-8.4 and dissolved oxygen >7 mg · L )1 . The induction time decreased and the recovery time increased with increasing concentrations. Conflicting results were found only in recovery time and there were no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…For 2‐PE, anesthesia induction resulted in a negative exponential relationship between concentration and time for induction, whereas time for recovery followed a polynomial function where higher concentrations resulted in increased recovery times. This pattern of variation was identical to the pattern described for other marine fish species, like great sturgeon, Huso huso , white sea bream, Diplodus sargus , sharp snout sea bream, Diplodus puntazzo , and meagre, A. regius (Tsantilas et al ; Serezli et al ; Shaluei et al ). But for other species, like Senegalese sole, Solea senegalensis , an opposite response was observed where higher doses of 2‐PE resulted in a shorter recovery period (Weber et al ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…For 2‐PE, anesthesia induction resulted in a negative exponential relationship between concentration and time for induction, whereas time for recovery followed a polynomial function where higher concentrations resulted in increased recovery times. This pattern of variation was identical to the pattern described for other marine fish species, like great sturgeon, Huso huso , white sea bream, Diplodus sargus , sharp snout sea bream, Diplodus puntazzo , and meagre, A. regius (Tsantilas et al ; Serezli et al ; Shaluei et al ). But for other species, like Senegalese sole, Solea senegalensis , an opposite response was observed where higher doses of 2‐PE resulted in a shorter recovery period (Weber et al ).…”
Section: Discussionsupporting
confidence: 84%
“…Fish progressed sequentially through the typical stages of anesthesia and recovery as described by Iwama et al (). The efficacy of these anesthetics for routine aquaculture practices have been studied in several fish species, some of which are listed in Table (Iwama et al ; Mylonas et al ; Tsantilas et al ; Weber et al ; Serezli et al ; Shaluei et al ). From these studies it can be concluded that anesthetic concentration changes with water temperature, fish species, and even fish size within the same species, reinforcing the importance of screening concentrations of anesthetics on new species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sedative and anaethetic agents are used in aquaculture to induce anaethesia during research experiments, blood sampling, biometric measuring, transport, tagging, controlled reproduction and surgery procedures, in order to reduce physiologic disturbances and physical injuries (Weber et al., ). After MS222 (Tricaine methane sulfonate), 2‐phenoxyethanol (2‐PE) is the most commonly used anaethetic in aquaculture (Serezli et al., ; Topic Popovic et al., ).…”
Section: Introductionmentioning
confidence: 99%